Karakterisasi Tokoh Utama dalam Novel Toraja Karya Endang SSN dan Implikasinya salam Pembelajaran Sastra si Sekolah - Arsadi, Nurlena; Bagtayan, Zilfa A. (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2025)
This research was conducted to describe the character of the main character reviewed from the setting, place, time, and atmosphere of the Toraja Novel by Endang SSN and its implications in literary learning in schools. The purpose of the research is to find out the character of the main character through a structural approach and implications in literary learning in schools. The theory used in this study is the theory of characterization. The research method used is a descriptive-analytical method. The source of data in this study was obtained from the novel Toraja by Endang SSN. The data collection technique in the study is using library studies, namely reading and identifying, the data analysis technique in this study is identifying, analyzing, descripting, and concluding. Based on the results of the research, information was obtained that the main character's character was reviewed from the setting, time, and atmosphere. It is concluded that the characterization of the main characters in the novel Toraja by Endang SSN is reviewed from the setting of the place including: In the car, on campus, at the airport, on the bus and in the market. Then the setting time includes: Sunday night. The atmosphere is tense, gripping, mystical and a happy atmosphere.